Studi Kepadatan Populasi Burung Endemik Timor di Sepanjang Jalur Patroli Desa Fatumnasi, Cagar Alam Mutis, Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur - Novianti Rosalia Abi; Maria M. E. Purnama; Fadlan Pramatana (Wana Lestari, 2023)
Birds are wild animals that play an important role in building the food chain, helping pollination, controlling insect pest populations, and seed dispersal agents that are useful for natural forest regeneration. An animal is said to be endemic if the species is a native species that can only be found in one place and not found in other places or areas as well as Endemic Birds that will be studied in the Mutis Nature Reserve Area. This study was conducted to determine the population density of Timor endemic birds along the Patrol Route to Padang I, Fatumnasi Village, Mutis Nature Reserve, South Central Timor Regency, East Nusa Tenggara Province. This research was conducted from April to May 2022. Data collection on the Population Density of Timor's Endemic Birds used the Point Count method. Bird population density data analysis used the Krebs formula and the Eisenberg formula. The results of this study recorded that 6 species of birds with the highest population density were Myzomela Timor (0.72 ind/ha), Timor Honeysucker (0.61 ind/ha), Timor Pergam (0.55 ind/ha), Opior Timor (0.50 ind/ha) and the lowest population density or the least in the Timor Kancilan (0.24 ind/ha) and Timor Anis (0.38 ind/ha). Over time, population density will decrease or increase according to the resilience of adaptation to changes in environmental conditions and competition with other organisms.